Current state and development prospects of the construction industry (Nexo Revista Científica, 2021)
The relevance of the research topic is due to the fact that construction companies in a difficult period in 2020 faced risk problems and many construction companies declared themselves bankrupt during this period. The globalization of the modern world defines more and more severe challenges for national economies around the world. Taking into account the modern patterns of development of the world economy, it is important for the national economy of each state to have a competitive advantage, thanks to which it will develop. The purpose of this article is to analyze the current state of the construction industry both in Russia and throughout the world, analyze existing problems, and develop measures aimed at solving them. In studying the economic situation of this industry, indicators such as volume dynamics were considered. construction works and the dynamics of the number of construction organizations. In addition, the work identified factors that limit the activities of construction organizations and the prospects for the development of the construction industry both in Russia and around the world. This paper defines actions to solve the problems of the construction industry, and also determines the expected results of the implementation of these measures. The construction industry also sets the level of economic development, is a very important sector in the economy of many countries of the world. The development of construction services all over the world has been gaining momentum in the past few decades and is developing very dynamically. However, the construction industry is very sensitive to even minor fluctuations in the global market. The subject of the research was the cause-and-effect relationships of the problems and prospects for the development of the construction industry both in Russia and at the global level in the context of the economic transformation of the world economy. In this paper, using SWOT data analysis, the strengths and weaknesses of the construction industry, threats and opportunities of the external environment in the modern conditions of development of both the Russian economy and the international market are analyzed. A working hypothesis of the study was formed. This hypothesis was tested in the framework of a scientific and practical seminar with the participation of representatives of universities that are engaged in the development of the construction industry, as well as with the participation of heads of construction companies. The article describes the current state of the construction industry in modern conditions of development both in Russia and abroad. A hypothesis is put forward about the impact of the crisis on the current state of the construction industry of the world market, measures are proposed to solve the identified problems of the development of the construction industry in Russia within the framework of the coordinated work of the authorities, universities of the country and business.